Exploring the Impact of Recruitment and Selection on Organizational Performance (Journal of Asian Development Studies, 2023)
The success of an organization depends on the recruiting and selection process, which involves selecting and hiring the best-qualified employees based on their abilities, experience, and skills. The study aimed to determine how hiring and firing practices affected organizational performance at higher education institutions (HEIs) in Southern KP, Pakistan. The study aimed to ascertain the effects of recruitment and selection on organizational performance at higher education institutions (HEIs) in KP's southern areas. In the south region of Khyber Pakhtunkhwa (KP), 330 respondents were chosen by stratified random sampling from public and private HEIs. The respondents (teachers), who filled out a closed-ended questionnaire, provided the information. The validity and reliability of the findings were investigated using SPSS. The results demonstrate that all hypotheses are accepted. The relationship between these factors was estimated and tested using simple linear regression. The study's conclusions showed that hiring and selecting employees directly impacted an organization's success. HEIs should focus on recruiting and hiring qualified staff to ensure that their performance meets the expectations of their clients. These findings will help HEIs, the government, and other stakeholders increase an organization's effectiveness. Finally, some exciting recommendations are given for HEI policymakers. The researchers also make some suggestions for additional research projects based on the current study's findings.